The Economic Consequences of Partisanship in a Polarized Era. Issue 1 (31st August 2017) - McConnell, Christopher; Margalit, Yotam; Malhotra, Neil; Levendusky, Matthew
Abstract: With growing affective polarization in the United States, partisanship is increasingly an impediment to cooperation in political settings. But does partisanship also affect behavior in nonpolitical settings? We show evidence that it does, demonstrating its effect on economic outcomes across a range of experiments in real‐world environments. A field experiment in an online labor market indicates that workers request systematically lower reservation wages when the employer shares their political stance, reflecting a preference to work for co‐partisans. We conduct two field experiments with consumers and find a preference for dealing with co‐partisans, especially among those with strong partisan attachments. Finally, via a population‐based, incentivized survey experiment, we find that the influence of political considerations on economic choices extends also to weaker partisans. Whereas earlier studies show the political consequences of polarization in American politics, our findings suggest that partisanship spills over beyond the political, shaping cooperation in everyday economic behavior.